Analysis of the effects of voltage pulses on P3HT:PCBM polymeric solar cells by means of TLP technique. (September 2018) - Buonomo, M.; Torto, L.; Barbato, M.; Wrachien, N.; Rizzo, A.; Gevorgyan, S.A.; Krebs, F.C.; Cester, A.
Abstract: We have studied the effects of an Electrostatic discharge stress on polymeric solar cells, employing P3HT:PCBM as active layer. All the analyzed devices featured a behavior strongly related to the evolution of the internal parasitic paths. We found that the degradation of the organic solar cells during the stress is related to the initial shunt condition. In addition, no breakdown occurred during the stress and only minor changes are visible from the photocurrent characteristics. Highlights: Effects of ESD pulses on P3HT:PCBM organic solar cells using TLP technique Evolutions of the parasitic shunts as consequence of ESD events Only marginal changes on the organic solar cells performances after the ESD stress No breakdown occurs in the organic solar cells after several ESD pulses.